(untitled) (Web of Teachers: Inderscience Research, 2025)
The process of teaching a foreign language occupies an important place in the modern education system. Today, the process of globalization, the development of international relations and the rapid growth of information technologies make learning foreign languages a more urgent issue. Communicative principles and new pedagogical technologies play an important role in foreign language teaching. This article provides information on the role of communicative principles and new pedagogical technologies in foreign language teaching.